(untitled) (Environment & Health, 2025)
The aim: Determination of the content of polonium-210 in tobacco cigarettes, which are present on the domestic market, and calculation of the radiation dose of smokers from smoking during one year. Materials and methods: 20 cigarettes of seven brands were randomly selected for the study. The weight of tobacco was weighed on an Adventurer АРС-120 scale with an accuracy of 0.01 g. Weighed samples were burned on an electric stove, then ashed in a muffle furnace at a temperature of 350ºС for 3-4 hours to «gray ash». The counting sample was weighed on the VLR 200 analytical balance. Since polonium-210 is the only alpha-emitter in tobacco, measurements of the total alpha activity were carried out on a radiometer for measuring small activities of UMF-2020. The minimum measured activity in the alpha channel in the counting sample during the measurement time of 3600 s (with a radiation background of no more than 0.2 μSv/h) at δ=50%, P=0.95 is no more than 0.02 Bq. All measuring equipment that was used in the study has calibration and meets the requirements of the methodology. For each study, the expanded uncertainty of the volumetric activity measurement was calculated. Results: As a result of research, it was established that the alpha-activity of tobacco is in the range of 0.029 - 0.099 Bq•g-1 (on average 0.06 Bq•g-1), the alpha-activity of tobacco of one cigarette is 0.023-0.081 Bq (on average 0.045 Bq). Since there are no other alpha-emitters in tobacco, it is assumed that this alpha-activity is explained by the presence of polonium-210. To determine the amount of polonium-210 retained by the filter during smoking, the alpha-activity of 20 filters after smoking 20 cigarettes was investigated. As a result of research, it was established that the filter retains about 0.01 Bq of polonium-210, that is, about 20% of the activity. Thus, if we assume that smokers smoke one pack of cigarettes per day, then in a year (365 days) 292 Bq of polonium-210 enters the lungs. The radiation dose, which was calculated taking into account the dose factor for 210 Po – 3•10-6 Sv/ Bq , was 0.88 mSv per year.